2020
DOI: 10.1007/s12630-020-01787-1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and safety of awake prone positioning COVID-19 patients with severe hypoxemic respiratory failure

Abstract: Purpose Prone positioning of non-intubated patients with coronavirus disease (COVID-19) and hypoxemic respiratory failure may prevent intubation and improve outcomes. Nevertheless, there are limited data on its feasibility, safety, and physiologic effects. The objective of our study was to assess the tolerability and safety of awake prone positioning in COVID-19 patients with hypoxemic respiratory failure. Methods This historical cohort study was performed across four hospitals in Calgary, Canada. Included pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 15 publications
4
53
0
6
Order By: Relevance
“…However, there are no prospective studies of sedation during prone positioning, whether NMBAs are used or not. The recent uncontrolled studies reported the feasibility and safety of prone ventilation in intubated ARDS patients under assisted breathing with a light sedation (volatile anesthetic agents) [62], and non-intubated patients without sedation [63].…”
Section: Analgesia and Sedation For Patients In The Prone Positionmentioning
confidence: 99%
“…However, there are no prospective studies of sedation during prone positioning, whether NMBAs are used or not. The recent uncontrolled studies reported the feasibility and safety of prone ventilation in intubated ARDS patients under assisted breathing with a light sedation (volatile anesthetic agents) [62], and non-intubated patients without sedation [63].…”
Section: Analgesia and Sedation For Patients In The Prone Positionmentioning
confidence: 99%
“…Reduction of respiratory rate with APP was demonstrated in ve studies (n = 90) [10,28,36,40,41], but not in two other studies (n = 34) [33,45]. Finally, signi cantly reduced PaCO2 was demonstrated only in a single small study (n = 9) [35], while no changes in PaCO2 were observed in a larger report (n = 46) [14].…”
Section: Resultsmentioning
confidence: 82%
“…Fifteen studies reported patients' tolerability to APP, varying from 47-100% [9, 10, 12, 14, 28-30, 32, 33, 35, 36, 40, 43, 45, 46]. Eight papers reported on patient's discomfort while in prone position [9,12,14,32,36,40,43,45], including back pain, dyspnea, and general discomfort. The daily duration of APP was reported in 17 papers (n = 366) [8-10, 12, 14, 28, 29, 31, 34, 36, 38, 40, 41, 45-47].…”
Section: Tolerability and Comfort Of Awake Prone Positioningmentioning
confidence: 99%
“…1,4,7,11,31 A Canadian prospective cohort study involving 4 hospitals in Calgary evaluated the safety and tolerability of prone positioning of patients who were not intubated on both the medical ward and in the ICU. 26 The study reported that 17 participants received a median of 2 (range 1-6) sessions of prone positioning for a median of 75 (range 30-480) minutes. Time spent prone was limited by back or shoulder pain (n = 2, 12%), general discomfort (n = 6, 35%) and delirium (n = 1, 6%).…”
Section: What Are the Potential Harms Of Prone Positioning?mentioning
confidence: 99%
“…There were otherwise no serious adverse events. 26 Whether prolonged prone positioning in patients with COVID-19 who are awake and not intubated increases the risk for venous thromboembolic disease is an important consideration, because observational studies have shown COVID-19 to be associated with an increased risk of venous thrombosis. 34 The published studies of prone positioning in nonintubated patients have sparsely reported on its harms.…”
Section: What Are the Potential Harms Of Prone Positioning?mentioning
confidence: 99%